2014
DOI: 10.1097/nnr.0000000000000056
|View full text |Cite
|
Sign up to set email alerts
|

Matching Doses of Distraction With Child Risk for Distress During a Medical Procedure

Abstract: Background Parents often want to provide support to their children during medical procedures, but not all parents are effective in providing distraction after brief training. Objective The aim of this study was to investigate the effects of three doses of distraction intervention for children at high and medium risk for procedure-related distress. Methods Children undergoing scheduled intravenous insertions for diagnostic or treatment purposes and their parents participated. A computerized application, Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…The provision of adult support through non-procedural talk and humor as a means of distraction, has been shown to be effective in improving children's coping during painful procedures, whilst reassuring comments, criticism, apologies, and entrusting children with too much control may increase distress (42). Parental coaching requires training of the parents, and children with high levels of fear may also need professional support (43). Research has shown that parents are often given information and supervision immediately before a procedure takes place, when they are distressed (44).…”
Section: Discussionmentioning
confidence: 99%
“…The provision of adult support through non-procedural talk and humor as a means of distraction, has been shown to be effective in improving children's coping during painful procedures, whilst reassuring comments, criticism, apologies, and entrusting children with too much control may increase distress (42). Parental coaching requires training of the parents, and children with high levels of fear may also need professional support (43). Research has shown that parents are often given information and supervision immediately before a procedure takes place, when they are distressed (44).…”
Section: Discussionmentioning
confidence: 99%
“…It also aimed to investigate the effects of distraction interventions for children at risk for procedure-related distress. The outcomes of this study validated the application for identifying parent-child dyads who were at varying levels of risk for distress during a medical procedure (McCarthy et al, 2014).…”
Section: Prior Research Findingsmentioning
confidence: 69%
“…Finally, this dissertation utilizes the data corpus from past research and, in consideration of this, I will provide an overview of those research findings and their implications (McCarthy et al, 2010a;McCarthy et al, 2010b;McCarthy et al, 2014). This will help define the context for the current study and the unique contributions it will provide.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations